Fluid-structure interaction enhances the aerodynamic performance of flapping wings: a computational study - Toshiyuki NAKATA; Ryusuke NODA; Hao LIU (Journal of Biomechanical Science and Engineering, 2018)
Insect wings change its shape passively by the aerodynamic and inertial forces when flapping, which can greatly affect its aerodynamic performances. In order to confirm the importance of the fluid-structure interaction in flapping wing aerodynamics, we performed computational fluid-structure interaction analyses of a hovering hawkmoth with ‘virtual’ vacuum conditions that can adjust the effect of the aerodynamic force on the deformation of flapping wings. It is turned out that the large part of the wing deformation, such as the wing twist, is induced by the inertial force as reported previously, but the adjustment of the wing deformation by the aerodynamic force can greatly affect the kinematics and the aerodynamics of flapping wings. While the wing deformation, regardless of the contribution of the aerodynamic force, can increase the aerodynamic power, force and efficiency of flapping wings, the wing deformation adjusted in response to the unsteady aerodynamics of flapping wings can further enhance the aerodynamic performance. These results not only reveal the influence of the wing deformation on the aerodynamic performance of flapping wings, but also point out the great importance of the fluid-structure interaction in the aerodynamics of insect flight and the design of bio-inspired micro aerial vehicles.